Mengatasi Stres Melalui Pariwisata dalam Novel SUNSET IN WEH ISLAND Karya Aida M.A. - Akbar Muttaqin; Dinavianti Dinavianti; Parrant Oryza Sativa; Eva Dwi Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out and find solutions experienced by the main character named Axel in dealing with stress and ways to overcome it. The novel chosen as the main focus is called Sunset In Weh Island by Aida M.A. This novel tells the story of a boy named Axel who was experiencing stress and many negative feelings, and is trying to find a way to calm his mind. He found the calming down method he needed after his trip to Weh Island. In this research, the descriptive method is used. It's a research method that relies on observations of documents, in this case a novel and some previous research articles. The approach method used is a hermeneutic approach. The data collection method uses reading techniques and note-taking techniques. The results obtained from this research are that the character Axel succeeded in overcoming the stress-causing problems he had because he went on a tourism trip.